Developmental progression of intellectual disability, autism, and epilepsy in a child with an IQSEC2 gene mutation. Issue 10 (24th August 2017) - Zipper, Rachelle; Baine, Sherri D.; Genizi, Jacob; Maoz, Hen; Levy, Nina S.; Levy, Andrew P.
Key Clinical Message: The neurodevelopmental progression of a school‐aged child with a spontaneous IQSEC2 mutation has demonstrated apparent regression of milestones and language. Seizures associated with the disorder have been refractory to medical treatment. Late treatment of autism in this child has led to improved social skills. Abstract : The neurodevelopmental progression of a school‐aged child with a spontaneous IQSEC2 mutation has demonstrated apparent regression of milestones and language. Seizures associated with the disorder have been refractory to medical treatment. Late treatment of autism in this child has led to improved social skills.